The realistic trend in Jafar Ali's films (Journal of the College of Basic Education, 2022)
Many of the great artists, when they complete their artistic works, they start from reality, as they can dispense with it, and yet they abhor the word realism. As Arjwan sees (that this comparison is the tragedy of vocabulary that creates a quotation in meaning, and therefore he decides to adhere to realism because the realistic position in life is the reason for my life and my art), and thus the importance of the research lies in the following:1- Determining the elements of the cinematic language of Jaafar Ali in dealing with reality.2- Detection of stylistic orientation